4(2x+1)-3x=19

Simple and best practice solution for 4(2x+1)-3x=19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+1)-3x=19 equation:


Simplifying
4(2x + 1) + -3x = 19

Reorder the terms:
4(1 + 2x) + -3x = 19
(1 * 4 + 2x * 4) + -3x = 19
(4 + 8x) + -3x = 19

Combine like terms: 8x + -3x = 5x
4 + 5x = 19

Solving
4 + 5x = 19

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 5x = 19 + -4

Combine like terms: 4 + -4 = 0
0 + 5x = 19 + -4
5x = 19 + -4

Combine like terms: 19 + -4 = 15
5x = 15

Divide each side by '5'.
x = 3

Simplifying
x = 3

See similar equations:

| 5x^2=6x+35 | | 176=6n+7(-8-5n) | | n+(-8)= | | X-x^2=-2 | | -4(4m-6)=-104 | | (5x+4y)2= | | 3+6w=-2w | | 7x+9.34=4x+13 | | -87=7+2(-7-5r) | | -48=-3c+9 | | 5x-3y-10=0 | | 12-3(5-1)= | | (-4.93)(-2.1)= | | .6y+1=1.4y-15 | | -126=6(-5+2n) | | 4x^2+26x+12=36 | | y+3=20 | | (39-2x)(21-2x)x=equation | | -5.79+3.11y-4.97-2.13y= | | 0.7x-12=-13.75 | | 10x+5=5(1+2x) | | 16+7r-8+7r=8r+5r | | 3(p-3)+7=32-4(2p+5) | | 4.5(x+7)=41.85 | | 34-6x=6-10x | | 4x+11=-49-6x | | (-8+3i)+(-5i)= | | 2+11x=-48+x | | X+12yi=3-6i | | (2x+1)(3-x)=0 | | 3(4x-1.5)-2x=17 | | 8*(x-2)=32 |

Equations solver categories